Proceedings of the 2017 ACM International Symposium on Symbolic and Algebraic Computation 2017
DOI: 10.1145/3087604.3087657
|View full text |Cite
|
Sign up to set email alerts
|

Big Prime Field FFT on the GPU

Abstract: We consider prime fields of large characteristic, typically fitting on k machine words, where k is a power of 2. When the characteristic of these fields is restricted to a subclass of the generalized Fermat numbers, we show that arithmetic operations in such fields offer attractive performance both in terms of algebraic complexity and parallelism. In particular, these operations can be vectorized, leading to efficient implementation of fast Fourier transforms on graphics processing units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Therefore, we consider the so-called generalized Fermat prime numbers. The detailed introduction of generalized Fermat prime numbers can be found in the previous work of our research group [5].…”
Section: Generalized Fermat Prime Fieldsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we consider the so-called generalized Fermat prime numbers. The detailed introduction of generalized Fermat prime numbers can be found in the previous work of our research group [5].…”
Section: Generalized Fermat Prime Fieldsmentioning
confidence: 99%
“…We consider prime fields of large characteristic, typically fitting on k machine words, where k is a power of 2. When the characteristic of these fields is restricted to a subclass of the generalized Fermat numbers, the authors of [5] have shown, in an ISSAC 2017 paper, that arithmetic operations in such fields offer attractive performance, both in terms of algebraic complexity and parallelism. In particular, these operations can be vectorized, leading to an efficient implementation of fast Fourier transforms on graphics processing units (GPUs), reported in that same paper.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations